Time to level the playing field between men and women - given similar injury incidence: a two-season analysis of match injuries in elite men and women's (super league) rugby league - Scantlebury, S.; Jones, B.; Owen, C.; Brown, J.; Collins, N.; Fairbank, L.; Till, K.; Phillips, G.; Stokes, K.; Whitehead, S. (Journal of Science and Medicine in Sport, 2024)
Objectives To compare match injury incidence, severity and burden in men's and women's elite rugby league.